Forty‐Year Analysis of Colonoscopic Surveillance Program for Neoplasia in Ulcerative Colitis: An Updated Overview. (July 2015) - Choi, Chang‐Ho Ryan; Rutter, Matthew D; Askari, Alan; Lee, Gui Han; Warusavitarne, Janindra; Moorghen, Morgan; Thomas‐Gibson, Siwan; Saunders, Brian P; Graham, Trevor A; Hart, Ailsa L
Abstract : Objectives: This study provides an overview of the largest and longest‐running colonoscopic surveillance program for colorectal cancer (CRC) in patients with long‐standing ulcerative colitis (UC). Methods: Data were obtained from medical records, endoscopy, and histology reports. Primary end points were defined as death, colectomy, withdrawal from surveillance, or censor date (1 January 2013). Results: A total of 1, 375 UC patients were followed up for 15, 234 patient‐years (median, 11 years per patient). CRC was detected in 72 patients (incidence rate (IR), 4.7 per 1, 000 patient‐years). Time‐trend analysis revealed that although there was significant decrease in incidence of colectomy performed for dysplasia (linear regression, R =−0.43; P =0.007), IR of advanced CRC and interval CRC have steadily decreased over past four decades (Pearson's correlation, −0.99; P =0.01 for both trends). The IR of early CRC has increased 2.5‐fold in the current decade compared with past decade (χ 2, P =0.045); however, its 10‐year survival rate was high (79.6%). The IR of dysplasia has similarly increased (χ 2, P =0.01), potentially attributable to the recent use of chromoendoscopy that was twice more effective at detecting dysplasia compared with white‐light endoscopy (χ 2, P <0.001). CRCs were frequently accompanied by synchronous CRC or spatially distinct dysplasia (37.5%). Finally, the risk of CRC was not significantly different between "indefinite" or low‐grade dysplasia (log‐rank, P =0.78). Conclusions: Colonoscopic surveillance may have a significant role in reducing the risk of advanced and interval CRC while allowing more patients to retain their colon for longer. Given the ongoing risk of early CRC, patients with any grade of dysplasia who are managed endoscopically should be monitored closely with advanced techniques.